Multichannel Speech Enhancement Approaches to DNN-Based Far-Field Speech Recognition - Delcroix, Marc; Yoshioka, Takuya; Ito, Nobutaka; Ogawa, Atsunori; Kinoshita, Keisuke; Fujimoto, Masakiyo; Higuchi, Takuya; Araki, Shoko; Nakatani, Tomohiro (New Era for Robust Speech Recognition, 2017)
In this chapter we review some promising speech enhancement front-end techniques for handling noise and reverberation. We focus on signal-processing-based multichannel approaches and describe beamforming-based noise reduction and linear-prediction-based dereverberation. We demonstrate the potential of these approaches by introducing two systems that achieved top performance on the recent REVERB and CHiME-3 benchmarks.